2016
DOI: 10.1111/epi.13510
|View full text |Cite
|
Sign up to set email alerts
|

Regional and global connectivity disturbances in focal epilepsy, related neurocognitive sequelae, and potential mechanistic underpinnings

Abstract: Epilepsy is among the most common brain network disorders, and it is associated with substantial morbidity and increased mortality. While focal epilepsy was traditionally thought of as a regional brain disorder, growing evidence has demonstrated widespread network alterations in this disorder which extend beyond the epileptogenic zone from which seizures originate. The goal of this review is to summarize recent investigations examining functional and structural connectivity alterations in focal epilepsy, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
116
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(129 citation statements)
references
References 76 publications
12
116
1
Order By: Relevance
“…It is useful to note that several previous investigations have demonstrated connectivity disturbances in widespread brain networks in TLE8; therefore, connectivity problems in this disorder are not specific to the ARAS alone. Interestingly, in the present study we did not observe significant connectivity differences between patients and controls related to certain other subcortical structures important for arousal, including thalamus and basal forebrain/nucleus accumbens (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…It is useful to note that several previous investigations have demonstrated connectivity disturbances in widespread brain networks in TLE8; therefore, connectivity problems in this disorder are not specific to the ARAS alone. Interestingly, in the present study we did not observe significant connectivity differences between patients and controls related to certain other subcortical structures important for arousal, including thalamus and basal forebrain/nucleus accumbens (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…It was supported by our present findings that the volumes of the corpus callous were significantly correlated with the mean diffusion measures, such as FA and MD. Although decreased global connectivity in focal epilepsy was already demonstrated by previous studies, it was not clear whether decreased global connectivity represents the damaging consequences of recurrent seizures or an adaptive mechanism to prevent seizure spread out of the epileptogenic zones (Englot et al, 2016). It was a plausible assumption from our study because global connectivity was associated with the adaptive mechanism for preventing seizures; patients with good responses to AEDs had high global connectivity.…”
Section: Discussionmentioning
confidence: 53%
“…Growing evidence has suggested that epilepsy is a network disease, and focal epilepsy, traditionally considered to be a regional brain disorder, also has widespread alterations of networks beyond the epileptogenic zone (Englot, Konrad, & Morgan, 2016). Many of the studies regarding brain connectivity in epilepsy have demonstrated that focal epilepsy is associated with increases in regional connectivity at the epileptogenic zone, paired with diminished global connectivity (Englot et al, 2016;Kim, Piao, Liu, Bingaman, & Diehl, 2008;Liu et al, 2015;Miro et al, 2015;Weber et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A by-product is that when abnormal interactions occur as in psychiatric disorders or after stroke or seizures (especially when involving the insula), abnormal cardiac regulatory activity may result. Although there is currently little evidence regarding network reconfiguration in these conditions, in focal epilepsy changes are described in network connectivity patterns (including the insula) [91,92]: interictal spikes affected the connectivity strengths between constituent network members. Similar changes could occur with other forms of aberrant cortical activity (generated by stroke or increased stress perception for example) which might dysregulate cardiac neural regulatory efferent activity resulting in the cardiopathic effects detailed in this review.…”
Section: The Insula Psychological Homeostasis and Cerebrogenic Cardimentioning
confidence: 99%